The reparation of damages to the victim of the crime in Spain vs Ecuador - Cárdenas Paredes, Karina Dayana (2023)
Reparation of damages is an obligation of the State, whose fundamental objective is to return the victim to the moment in which he/she was before the violation of his/her rights, for which reason measures have been developed to repair the damages caused, which will depend on whether they are of a material or immaterial nature. The general objective of this article is to analyze, comparatively and critically, the comprehensive reparation of damages as a criminal legal institute, which is regulated in Spain and Ecuador, respectively. In order to achieve the research result, research methods such as literature review, historical-logical, documentary analysis and inductive-deductive methods have been used, which have allowed us to confirm that the two forms of legal regulation of reparation comply with the purpose of helping to repair the damages to the victims of crimes, however, more mechanisms should be developed to compensate the damage through the Administration of Justice and to comply with the duty to protect the fundamental rights that as human beings belong to us.